Reporting two novel Kluyvera species, Kluyvera huaxiensis and Kluyvera chengduensis, isolated from human sputa - Liu, Lina; Feng, Yu; Wen, Hongxia; Zong, Zhiyong (Frontiers in Microbiology, 2026)
IntroductionTwo Gram-stain negative, facultatively anaerobic, rod-shaped, motile, and non-spore forming bacterial strains, 142053T and 142359T, were isolated from sputum samples obtained from different patients.MethodsGrowth of strain 142053T and 142359T occurred at 8–42 °C (optimum 28–37 °C), pH 5.0–9.0 (optimum 6.0–8.0) and NaCl concentrations of 0–5% (w/v) (optimum 0–4%). Comparison of 16S rRNA gene sequences showed that strain 142053T and 142359T exhibited high similarity to Kluyvera intermedia NBRC 102594T (99.48%) and Kluyvera georgiana ATCC 51603T (98.68%), respectively.ResultsPhylogenomic tree of species from family Enterobacteriaceae revealed that strain 142053T and 142359T formed distinct branches within the Kluyvera clade. The digital DNA–DNA hybridization between 142053T, 142359T, and all type strains of Kluyvera species were ≤39.5% and ≤54.7%, respectively, and the corresponding average nucleotide identity were ≤90.56% and ≤93.85%, both below the species delineation threshold. The two strains differ phenotypically from other Kluyvera species by their lipase and arginine dihydrolase utilization and from each other by ᴅ-arabitol utilization. The predominant fatty acids identified in both strains were C16:0, summed feature 3 (C16:1ω7c/C16:1ω6c), summed feature 8 (C18:1ω7c) and C17:0 cyclo.DiscussionBased on the phenotypic, chemotaxonomic, phylogenetic and genomic evidence, strains 142053T and 142359T represent two novel species of the genus Kluyvera, for which the names Kluyvera huaxiensis sp. nov. and Kluyvera chengduensis sp. nov. are proposed, with type strains 142053T (= GDMCC 1.4845T = JCM 37413T) and 142359T (= GDMCC 1.5094T = JCM 37737T), respectively.